2018
DOI: 10.1371/journal.pone.0206146
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for acute contraction-induced myokine secretion by C2C12 myotubes

Abstract: Skeletal muscle is considered a secretory organ that produces bioactive proteins known as myokines, which are released in response to various stimuli. However, no experimental evidence exists regarding the mechanism by which acute muscle contraction regulates myokine secretion. Here, we present evidence that acute contractions induced myokine secretion from C2C12 myotubes. Changes in the cell culture medium unexpectedly triggered the release of large amounts of proteins from the myotubes, and these proteins ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…Gene expression results show that EGR1, IL6, FOS, HSPB1, and mdm2 increased after 20-Hz EPS. These genes were known to increase after exercise or EPS ( Furuichi et al., 2018 ; Irrcher and Hood, 2004 ; Neubauer et al., 2014 ; Roudier et al., 2012 ). Gene expression of dgkq, Pik3r1, PIK3C2B, and Thbs1 decreased after 20-Hz EPS.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression results show that EGR1, IL6, FOS, HSPB1, and mdm2 increased after 20-Hz EPS. These genes were known to increase after exercise or EPS ( Furuichi et al., 2018 ; Irrcher and Hood, 2004 ; Neubauer et al., 2014 ; Roudier et al., 2012 ). Gene expression of dgkq, Pik3r1, PIK3C2B, and Thbs1 decreased after 20-Hz EPS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies reported that the change of IL-6 in muscle and in circulation is not consistent [5,6,10,27]. Furuichi et al also have reported that IL-6 release from C2C12 cells which is the murine-derived skeletal muscle cell line is induced by electrical stimulation independently of intracellular IL-6 protein levels of C2C12 cells lysate [9]. These studies suggest that muscle IL-6 release is induced independently of the transcription.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IL-6 is produced by myocytes during endurance exercise [6,8]. Electrical stimulation of C2C12 cells (a murine-derived skeletal muscle cell line) also stimulates IL-6 production in vitro [9]. However, IL-6 exists in interstitial spaces, as detected by immunohistochemistry [6], suggesting that non-myocyte cells may also produce IL-6.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid concentration in the medium increased due to contraction (Fig 1C), while glucose concentration decreased (Fig 1D). We have previously shown that acute contractions by 1 h EPS induced IL-6 and IL-15 secretions from C2C12 myotubes in Krebs Ringer bicarbonate (KRB) buffer [18]. However, the amount of IL-6 and IL-15 in the medium was unchanged under the present EPS protocol (Fig 1E and 1F).…”
Section: Plos Onementioning
confidence: 56%
“…The secretion of IL-6 and IL-15 was unchanged under the present EPS protocols ( Fig 1E and 1F ). The difference may depend on the medium, as KRB buffer, rather than DMEM, is suitable for detecting IL-6 secretion [ 18 ]. Regardless, it is unlikely that these proteins affected adipogenesis or lipolysis in the present experiment system, even though it has been reported that IL-6 and IL-15 reduce adiposity [ 6 9 ].…”
Section: Discussionmentioning
confidence: 99%